Effectiveness of Debating Method in Teaching Advanced English Speaking for Non English Department Students - Arum Sari; Saly Kurnia Octaviani; Suryanti Galuh Pravitasari (International Journal of English Linguistics, Literature, and Education (IJELLE), 2020)
AbstractCollege students in higher levels of semester from non English department require advanced stage of learning English method. Therefore, this research takes English debating as advanced English learning method for non English Department students. Aims of this research are (1) to present the students’ score of English speaking skill in debating performance; and (2) to explain the effectiveness of debating method in teaching advanced English speaking based on lecturer’s and college students’ point of view. This research applies qualitative descriptive to present statistical data form and purposive sampling technique for selecting the respondents. This research took 30 students of fifth grade at STMIK Sinar Nusantara Surakarta in academic year 2018/2019. In this research, 5% students scored 50, 18 % students scored 60, 42% students scored 70, and 32% students scored 80 for the fluency aspect. From the accuracy aspect, 12% scored 50, 25% students scored 60, 35% students scored 70, and 28% students scored 80. From the pronunciation aspect, 10% students scored 50, 22% students scored 60, and 38% students scored 70, and 30% students scored 80. From the intonation aspect, 10% students scored 50, 30% students scored 60, 40% students scored 70, and 20 % students scored 80. As a conclusion, debating method is effective for teaching advanced English speaking for non English department students in higher semester.  Keywords: Advanced English, Advanced English Learning, English Learning, English Learning Method, English Debating, Leaning English by Debating